Equilibrium Exchange Rates in Transition Economies: Taking Stock of the Issues - Balázs Égert; László Halpern; Ronald MacDonald (Oesterreichische Nationalbank (OeNB), 2005)
In this paper we present an overview of a number of issues relating to the equilibrium exchange rates of transition economies of the former soviet bloc. In particular, we present a critical overview of the various methods available for calculating equilibrium exchange rates and discuss how useful they are likely to be for the transition economies. Amongst our findings is the result that the trend appreciation usually observed for the exchange rates of these economies is affected by factors other than the usual Balassa-Samuelson effect, such as the behaviour of the real exchange rate of the open sector and regulated prices. We then consider three main sources of uncertainty relating to the implementation of an equilibrium exchange rate model, namely: differences in the theoretical underpinnings; differences in the econometric estimation techniques; and differences relating to the time series and cross-sectional dimensions of the data. The ensuing three-dimensional space of real misalignments is probably a useful tool in determining the direction of a possible misalignment rather than its precise size.
Keywords: C15; E31; F31; O11; P17; 330; equilibrium exchange rate; Purchasing Power Parity; trend appreciation; Balassa-Samuelson